Indium Recovery from End-of-Life E-Waste: Important Details Related to Spectroanalytical Determination and Recycling Viability - Castro, Jeyne Pricylla; Garcia, José Augusto; Souza, Ricardo G. [UNESP]; Pereira-Filho, Edenir R. (Sociedade Brasileira de Quimica (SBQ), 2024)
Recycling has experienced great interest over the past five years, primarily driven by its strategic economic significance and the growing scarcity of natural resources. One element that has garnered attention is indium (In), especially due to its presence in flat panel displays (FPDs), particularly in devices utilizing liquid crystal display (LCD). The goal of this research was to establish a method for extracting In from LCD. The study faced challenges related to In determination using inductively coupled plasma optical emission spectroscopy (ICP OES), and furthermore, it proposed an optimized extraction method through design of experiments (DoE), focusing on extraction time and percentage of solid variables. Diverse sample types encompassing smartphones, monitors, and television screens were processed. Leaching was conducted utilizing a magnetic plate at 80 °C, employing a 1 mol L-1 H2SO4 solution along with 25% m v-1 of the sample. This proposed method achieved a near-complete extraction rate (100%) for In. Moreover, in-depth interviews were conducted with several stakeholders in urban mining and various sectors within Brazil. The insights gleaned from these interviews showed the absence of a consolidated market for recycling LCDs with a specific emphasis on In recovery.
Keywords: design of experiment; extraction rate; In recovery; LCD; optimization